KARAKTERISTIK PENDERITA BRONKITIS YANG DIRAWAT JALAN PADA KELOMPOK UMUR ≥ 15 TAHUN DI RSU DR.FERDINAN LUMBAN TOBING SIBOLGA TAHUN 2010-2012 KARAKTERISTIK PENDERITA BRONKITIS YANG DIRAWAT JALAN PADA KELOMPOK UMUR ≥ 15 TAHUN DI RSU DR.FERDINAN LUMBAN TOBIN - Rinaldi Togap Simanjuntak; drh. Rasmaliah,M.Kes; Drs Jemadi,M.Kes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Bronchitis is described as inflammation of the bronchial vessels. It is characterized by inflammation of the bronchial tubes and divided into acute and chronic forms. Indonesia does not have accurate data on morbidity of acute or chronic bronchitis. Bronchitis including ten biggest disease in the outpatient Dr. Ferdinand L. Tobing General Hospital. Total cases of bronchitis in 2010-2012 there were 442 cases. To determine the characteristics of patients with bronchitis outpatient from 2010 until 2012 conducted a descriptive study design case series. The Populations in this study as much as 442 data and the samples in this study as much as 206 data obtained by sampling random tables C.Survey program, data analysis by using Chi-square test. Results showed that the highest proportion with bronchitis in the age group 24-32 years 21,8%, for male gender in the age group of 24-32 years 22,6%, for female gender in the age group of 42-50 years 25,6%, 19,4% self-employed jobs, with marital status 75,2%, residence in Sibolga 63,6%, 100% clinical symptoms of cough, chronic bronchitis type 58,3%, 61,7% smoking history, number of visits ≤ 4 times 78,2% and other general expenses 51,5%. Statistical test results showed there is significant difference proportion between of patients aged by type of bronchitis (p <0,05), gender by type of bronchitis (p <0,05), sex based on a history of smoking (p <0,05), and bronchitis type by type of smoking history (p<0,05). There is no significant difference proportion between of patients aged by a history of smoking (p> 0.05) and the number of visits by source of funding (p> 0.05). Expected to bronchitis sufferers to increase body resistance, hygiene, environmental sanitation and reduce smoking and the doctors and nurses Dr. Ferdinand L.Tobing General Hospital Sibolga to give understanding to patients and their families about the disease bronchitis. Keywords: Bronchitis, Caractheristic of patient, Dr. Ferdinand L.Tobing General Hospital.